1977
DOI: 10.1002/ijc.2910190103
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin complexes in sera of patients with malignancy

Abstract: Sera frour 146 patients with malignancy, 59 normal controls and 42 patients hospitalized with non-malignant diseases were examined by a precipitin test with monoclonal rheumatoid factor (mRF) for the presence of circulating immune complexes containing IgG. Forty-two (29%) of the sera from cancer patients but only two of the sera from patients in each of the control groups contained such material. Similar results were obtained with a radioimmunoassay for immune complexes based on the same mRF. Sera from 23 of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

1979
1979
1989
1989

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 27 publications
2
23
0
2
Order By: Relevance
“…The findings reported herein on the incidence of serum IC in BC patients are consonant with those from other investigators [7,11,14,16,17], although some groups using Clq-binding assays have reported a greater incidence and higher levels of IC [3,12,13]. Assays that are based on the precipitation or deviation of radiolabeled Clq may overestimate the incidence of IC, since polyanions have the ability to bind to Clq [3,12].…”
Section: Discussionsupporting
confidence: 90%
“…The findings reported herein on the incidence of serum IC in BC patients are consonant with those from other investigators [7,11,14,16,17], although some groups using Clq-binding assays have reported a greater incidence and higher levels of IC [3,12,13]. Assays that are based on the precipitation or deviation of radiolabeled Clq may overestimate the incidence of IC, since polyanions have the ability to bind to Clq [3,12].…”
Section: Discussionsupporting
confidence: 90%
“…10. 22], rheumatoid factors [7] and the Raji cell assay [2], Depending on the study and the assay used, from 16 to 83% of the cancer patients tested had CIC. The incidence can vary widely with the tumor tested, its staging, as w'ell as the assay used.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there have been numerous reports describing the presence of immune complexes (IC) in the blood and on the surface of tumor cells of patients with malignant disease [1][2][3][4]. Such complexes have al so been reported in effusions associated with both breast cancer [5] and lung cancer [6].…”
Section: Introductionmentioning
confidence: 99%